Efektivitas Penggunaan Video Pembelajaran untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran Sejarah Kebudayaan Islam - Foni Indriyani (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2026)
This research is based on the low interest of students in learning Islamic cultural history, which usually only uses the lecture method. The monotonous delivery of material makes it difficult for students to absorb the content, even though the scope of Islamic cultural history material is very broad. This study aims to analyze the role and effectiveness of using video media in increasing student enthusiasm as well as its impact on learning outcomes. This research uses the systematic literature review method by identifying and analyzing 15 relevant journals from the period 2020-2026 sourced from Google Scholar. The analysis shows that the use of learning videos has been proven effective in improving student learning outcomes in the SKI subject. In addition to improving academic achievement, learning videos play an important role in providing more concrete visualizations, increasing interest and motivation to learn, stimulating active student participation, and creating an interactive and meaningful learning atmosphere compared to conventional methods. Nonetheless, challenges in the field are still found regarding the limitations of technological devices and teachers' readiness in digital adaptation.